2020
DOI: 10.3386/w27612
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating During Coronavirus: The Impact of COVID-19 on the Nature of Work

Abstract: The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 0 publications
4
80
0
3
Order By: Relevance
“…Most research so far has been devoted to how the pandemic has altered employee productivity ( 3 , 4 ). A survey of 4,535 principal investigators revealed that female scientists with young children living at home experienced a decline in time spent on research ( 5 ).…”
mentioning
confidence: 99%
“…Most research so far has been devoted to how the pandemic has altered employee productivity ( 3 , 4 ). A survey of 4,535 principal investigators revealed that female scientists with young children living at home experienced a decline in time spent on research ( 5 ).…”
mentioning
confidence: 99%
“…First, what we know of work practices during the COVID-19 is very limited despite more than one third of the U.S. workforce transitioned to WFH during the pandemic [1] -and many believe that WFH is here to stay [5]. Yet, empirical studies on the topic is very rare [4,6,29,30]. Accordingly, our first contribution is providing insights on a phenomenon that has become very prevalent but very less known.…”
Section: Resultsmentioning
confidence: 99%
“…Second contribution of this study is that it employs ICT (information and communication technologies) data while most prior studies were self-report based, and therefore suffer from well-known survey issues such as selectivity biases, response biases, and item-characteristic biases [31]. The only other work that uses ICT metadata for analyzing the effect of mandatory WFH is [29]. Although that study is sound from an external validity perspective, their data is at metropolitan area level and did not give itself in to analyze any heterogeneity effect of WFH on communication patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on productivity of the current shock is unknown. Newly-remote urban office workers work longer days, have more, but shorter, meetings and do more email (DeFilippis et al., 2020). While 29% of workers in Felstead and Reuschke’s survey report higher output, 30% say it had fallen.…”
Section: Remote Possibilitiesmentioning
confidence: 99%